Controlled and scalable torsional actuation of twisted nylon 6 fiber. Issue 13 (12th March 2016) - Aziz, Shazed; Naficy, Sina; Foroughi, Javad; Brown, Hugh R.; Spinks, Geoffrey M.
ABSTRACT: Large‐scale torsional actuation occurs in twisted fibers and yarns as a result of volume change induced electrochemically, thermally, photonically, and other means. A quantitative relationship between torsional actuation (stroke and torque) and volume change is here introduced. The analysis is based on experimental investigation of the effects of fiber diameter and inserted twist on the torsional stroke and torque measured when heating and cooling nylon 6 fibers over the temperature range of 26–62 °C. The results show that the torsional stroke depends only on the amount of twist inserted into the fiber and is independent of fiber diameter. The torque generated is larger in fibers with more inserted twist and with larger diameters. These results are successfully modeled using a single‐helix approximation of the twisted fiber structure. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1278–1286 Abstract : The torsional actuation in twisted polymer fibers is the basis of recently described high‐performance artificial muscles. Here, the thermally induced rotation by partial untwisting of nylon 6 fibers is evaluated to establish the scaling relationships. Various diameter monofilaments with different amounts on inserted twist were investigated and a quantitative relationship describing the torsional actuation is developed. The model is based on a single‐helix approximation and predicts both the amount of rotation and the torque generated with high accuracy.